Estrutura do capim-braquiária durante o diferimento da pastagem - Santos, Manoel Eduardo Rozalino; Da Fonseca, Dilermando Miranda; Gomes, Virgilio Mesquita; Balbino, Eric Márcio; Magalhães, Marcela Azevedo [UNESP] (Universidade Estadual de Maringa, 2010)
This experiment was performed aiming to evaluate tiller population density, forage mass and its morphological components on pastures of Brachiaria decumbens cv. Basilisk. during deferment. The treatments encompassed four deferred grazing periods (18, 46, 74 and 121 days). A randomized block design with two replications was used. The numbers of vegetative tillers (VT), reproductive tillers (RT) and dead tillers (DT) in the pasture were determined. The masses of green leaf blade (GLBM), dead stem (DSM) and dead forage (DFM) were also determined. There was a reduction in the number of VT (from 1, 491 to 944 tiller m-2) during the deferment period. RT and DT numbers were not influenced by the deferment periods. Their averages were 211 and 456 tiller m-2, respectively. Longer deferring periods resulted in an increase in GSM (from 2, 965 to 4, 877 kg ha-1 of dry mass) and DFM (from 2, 324 to 4, 823 kg ha-1 of dry mass), but it did not influence GLBM (average of 2, 047 kg ha-1 of dry mass). In Viçosa, Minas Gerais State Brazil, Brachiaria decumbens cv. Basilisk pasture fertilized and deferred in the beginning of March must be kept deferred for about 70 days in order to conciliate both quality and quantity forage production.
Signalgrass structure during pasture deferment
Keywords: Brachiaria decumbens; Forage mass; Morphological composition; Tiller population density; Brachiaria; Urochloa brizantha